(untitled) (Web of Teachers: Inderscience Research, 2023)
The article deals with the role of importance of individual psychological characteristics of a person in sports phycology lesson. In particular, the problem of abilities is first of all related to the quality of human intelligence, the presence of skills, abilities and knowledge in it.